Learning Support Assistants’ (LSAs’) Roles, Professional Development Experiences and Training Needs in Private Schools in the Emirate of Dubai - BALASUBRAMANIAN, RAJASHREE (2025)
This study examines the roles, professional development experiences, and training requirements of Learning Support Assistants (LSAs) at private schools in Dubai. LSAs are crucial in aiding students with special educational needs (SEN) in inclusive classrooms. However, concerns persist regarding their training, clarity of roles, and integration into the wider school environment. Data was gathered from 54 LSAs via a survey that included both closed and open-ended questions. The research aimed to understand the demographics of LSAs, their roles, the professional development opportunities available, and the barriers they face in obtaining further training. Findings indicate that while LSAs in Dubai are generally well-qualified and trained compared to their international peers, issues with role clarity, collaboration with classroom teachers, and access to structured professional development persist. They reported a need for training in behaviour management, teaching strategies, and facilitating peer interactions but identified significant barriers such as time constraints, financial issues, and lack of institutional support. The study highlights the need for schools and policymakers to define LSAs' roles clearly and provide individualised training programs along with adequate supervision to boost their effectiveness. Recommendations include integrating professional development into school hours, fostering greater collaboration between LSAs and teachers, and further clarifying LSAs' duties to improve their function in inclusive classrooms.